Analysis of Sentence Types Found in Stephen Crane’s Short Story A Dark Brown Dog - Febrianti, Marsela; Sudar, Sudar; Widodo, Sri (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2024)
English is a global language for communication, and it's essential to develop four critical skills: listening, speaking, reading, and writing. In writing, using the right words and sentence structure is crucial. This research analyzed the sentence structures in Stephen Crane's short story A Dark Brown Dog. The study employs a descriptive and qualitative approach to explore the roles of different sentence types within the narrative and their potential applications in writing instruction. The data for this analysis was derived from Stephen Crane's short story A Dark Brown Dog. The results showed that there are four types of sentences in the story. Out of 144 sentences, 69 are simple (47.22%), 11 are compound (7.64%), 51 are complex (35.41%), and 14 are compound-complex (9.72%). These sentence types can help teach writing.